2005
DOI: 10.1210/en.2004-1290
|View full text |Cite
|
Sign up to set email alerts
|

Development, Maintenance, and Function of the Adrenal Gland in Early Postnatal Proopiomelanocortin-Null Mutant Mice

Abstract: Adult mouse mutants homozygous for an engineered proopiomelanocortin (POMC)-null allele lack macroscopically distinct adrenal glands and circulating adrenal hormones. To understand the basis for this adrenal defect, we compared the development of adrenal primordia in POMC-null mice and littermate controls. POMC-null mutant mice are born with adrenal glands that are morphologically indistinguishable from those of their wild-type littermates. However, in mutants adrenal cells fail to proliferate postnatally and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 46 publications
(48 reference statements)
3
51
1
2
Order By: Relevance
“…2 A), suggesting that the proliferation of zF in MC2R KO mice was comparable with that in WT mice. In contrast, it was previously demonstrated that adrenal glands of POMC KO mice on postnatal day 14 had reduced proliferating cell nuclear antigen (PCNA)-positive cells (21). These differences could be explained by the possible role of POMCderived peptides other than ACTH in adrenal development (22), although we could not exclude the possibility of difference due to genetic background or of compensatory function by other MCRs in the absence of MC2R.…”
Section: Discussioncontrasting
confidence: 66%
“…2 A), suggesting that the proliferation of zF in MC2R KO mice was comparable with that in WT mice. In contrast, it was previously demonstrated that adrenal glands of POMC KO mice on postnatal day 14 had reduced proliferating cell nuclear antigen (PCNA)-positive cells (21). These differences could be explained by the possible role of POMCderived peptides other than ACTH in adrenal development (22), although we could not exclude the possibility of difference due to genetic background or of compensatory function by other MCRs in the absence of MC2R.…”
Section: Discussioncontrasting
confidence: 66%
“…A carefully conducted study by Ute Hochgeschwender's group (Karpac et al 2005) showed that the adrenals in the Pomc null mice developed normally but subsequently underwent atrophy after birth due to a lack of cellular proliferation rather than apoptosis. The authors also attempted to acutely stimulate the adrenals in young Pomc null mice with 1µg of ACTH and found that although the adrenals at this stage appeared relatively normal, expressing both the ACTH receptor and components of the steroidogenic pathway, they found (as in the earlier study by Smart and Low) that the adrenals were not capable of secreting any corticosterone.…”
Section: The Pomc -/-Mousementioning
confidence: 99%
“…Adrenalectomy and subsequent adrenal transplantations were carried out as previously described (van der Sluis et al 2012). At postnatal day 10, adrenal glands were isolated from female donor LDLR knockout or C57BL/6 pups to serve as transplant donors (Karpac et al 2005). Eight-to 10-week-old female recipient LDLR knockout mice were bilaterally adrenalectomized under isoflurane inhalation anesthesia through a dorsal midline skin incision and lateral retroperitoneal incisions.…”
Section: Adrenal Transplantationmentioning
confidence: 99%